Synthesis, Characterization, Antioxidant Activity and Conformational Study of 4-Hydroxychalcone - André Luis Kerek; Thiago de Castro Rozada; Barbara Celânia Fiorin (Orbital: The Electronic Journal of Chemistry, 2021)
The objective of this work was to develop a synthesis, characterization, and conformational study of 4-hydroxychalcone. The chalcone was obtained using Claisen-Schmidt reaction. The product was characterized by IR and NMR spectroscopy. The latter technique was extremely important to verify the presence of the vinyl double bond formed in the reaction and to determine its trans configuration. The antioxidant activity of 4-hydroxychalcone showed a satisfactory result when compared to antioxidants already reported in the literature, with 63.4% inhibition of the DPPH radical. Also, theoretical calculations were performed to determine conformational preference. The s-cis (b) (52.0%) and the s-cis (a) (35.0%) conformers showed less energy when compared to s-trans conformers, due to the higher stabilizing effect of electron delocalization involving the p orbitals resulting from the higher planarity of s-cis conformers. However, the s-cis (a) conformer showed greater stabilization energy (510.37 kcal mol-1) in relation to the s-cis (b) conformer (505.32 kcal mol-1), this fact might be explained by the hydroxyl group interaction with the aromatic ring B, as observed by the NBO calculations.